(untitled) (Transport systems and technologies, 2020)
An analytical overview of Ukraine’s grain production volumes is presented, the dynamics and geography of the grain export of Ukraine are analyzed. The most part of the frown grain is exported from Ukraine and, as well as the grain production, the export structure is formed from wheat, corn and barley. The geography of export differs for these kings of grain products, however, key markets are separated (?) from Ukraine with sea. There are Asian and North-Africa countries and countries of the Middle East, which are depended from grain import traditionally. The transportation of grain turnovers thus is carried by maritime transport. This is Testify to this are significant volumes of handling of grain cargoes in national seaports and terminals operating in them. Тhe main grain ports are considered to be Mykolaiv, Odesa, Pivdennyi and Chornomorsk with their total share up to 90% of general grain export. In less volumes grain cargoes are handled in Kherson, Berdyansk and Mariupol’. For most Ukrainian ports grain is a strategic cargo, providing up to half of their cargo turnover.